2011
DOI: 10.1177/1553350611411491
|View full text |Cite
|
Sign up to set email alerts
|

Autostereoscopic Three-Dimensional Viewer Evaluation Through Comparison With Conventional Interfaces in Laparoscopic Surgery

Abstract: In the near future, it is likely that 3-dimensional (3D) surgical endoscopes will replace current 2D imaging systems given the rapid spreading of stereoscopy in the consumer market. In this evaluation study, an emerging technology, the autostereoscopic monitor, is compared with the visualization systems mainly used in laparoscopic surgery: a binocular visor, technically equivalent from the viewer's point of view to the da Vinci 3D console, and a standard 2D monitor. A total of 16 physicians with no experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 21 publications
(27 reference statements)
0
15
0
Order By: Relevance
“…In a recent laboratory‐based study, Silvestri et al . compared 2D, binocular 3D and 3D autosteroscopic displays. The auto‐stereoscopic display provided results comparable with binocular 3D, but necessitated more training.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent laboratory‐based study, Silvestri et al . compared 2D, binocular 3D and 3D autosteroscopic displays. The auto‐stereoscopic display provided results comparable with binocular 3D, but necessitated more training.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study confirmed the importance of stereoscopic viewing in improving performance, and underlined the subjective estimation of task efficiency. In a recent laboratory-based study, Silvestri et al (16) compared 2D, binocular 3D and 3D autosteroscopic displays. The auto-stereoscopic display provided results comparable with binocular 3D, but necessitated more training.…”
Section: D 3d and Stereoscopic Viewingmentioning
confidence: 99%
“…The role of newly designed HD, stereoscopic 3D visualization system in overcoming the drawbacks of 2D system is worth investigating [22]. Silvestri et al have reported that the main problem with these studies was that they compared low-resolution 3D displays with high definition 2D [16]. Previous studies comparing 2D and 3D LVS have been limited by the technology available, and several studies have failed to demonstrate statistically significant improvement in performance or accuracy with 3D compared to 2D imaging [2,18,[23][24][25][26].…”
Section: Discussionmentioning
confidence: 97%
“…10 Several studies have suggested that 3D imaging facilitates the execution of complex tasks with improved performances. [11][12][13][14][15][16] Previous studies 17,18 have suggested that 3D would not provide any benefits for experienced surgeons, due to their extensive experience with 2D laparoscopy. On the other hand, other recent studies have successfully shown improved performances of experienced surgeons when 3D imaging was used.…”
Section: Introductionmentioning
confidence: 99%